2017
DOI: 10.1093/nar/gkx915
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide prediction of minor-groove electrostatic potential enables biophysical modeling of protein–DNA binding

Abstract: Protein–DNA binding is a fundamental component of gene regulatory processes, but it is still not completely understood how proteins recognize their target sites in the genome. Besides hydrogen bonding in the major groove (base readout), proteins recognize minor-groove geometry using positively charged amino acids (shape readout). The underlying mechanism of DNA shape readout involves the correlation between minor-groove width and electrostatic potential (EP). To probe this biophysical effect directly, rather t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
76
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 73 publications
(81 citation statements)
references
References 72 publications
3
76
0
2
Order By: Relevance
“…Several studies have suggested that DNA shape, including MGW and electrostatic potential, contributes to specific DNA recognition 33,36,37 . Our experiments show that the CTCTGTTTT motif has the highest binding affinity, while other CTCTGYTY motifs are weaker.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have suggested that DNA shape, including MGW and electrostatic potential, contributes to specific DNA recognition 33,36,37 . Our experiments show that the CTCTGTTTT motif has the highest binding affinity, while other CTCTGYTY motifs are weaker.…”
Section: Discussionmentioning
confidence: 99%
“…2. Average DNA shape feature values within the same window, computed using the R package DNAshapeR v1.5.3 (Chiu et al 2017). Thirteen DNA shape features were used in this study (Sagendorf et al 2017), along with predicted minor-groove electrostatic potential (Chiu et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…For modeling of nucleosomal symmetry patterns at enhancers, DNA sequences were extracted from the reference genome (mm9) and scored as follows. Three sets of features were considered: (1) DNA sequence content encoded as k-mers (2 ≤ k ≤ 4) within 450 bp upstream of and downstream from the PU.1 summit; (2) average DNA shape feature values within the same window, computed using the R package DNAshapeR version 1.5.3 (Chiu et al 2017)-13 DNA shape features were used in this study (Sagendorf et al 2017), along with predicted minor groove electrostatic potential (Chiu et al 2017); (3) transformed FIMO P-values [−10 * log 10 (p)] (Grant et al 2011) for a curated collection of >1700 position weight matrices (PWMs) representing mammalian TF motifs (Diaferia et al 2016), core promoter elements, 5 ′ splice site, and PAS motifs-these were computed within 300 bp of the PU.1 summit as described previously (Barozzi et al 2014) using FIMO from MEME version 4.11.3.…”
Section: Statistical Learningmentioning
confidence: 99%